Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1089/ham.2007.8407
|View full text |Cite
|
Sign up to set email alerts
|

Residents at High Altitude Show a Lower Glucose Profile Than Sea-Level Residents Throughout 12-Hour Blood Continuous Monitoring

Abstract: It is known that residents at high altitude (HA) have a lower basal glycemia than residents at sea level (SL). However, whether such a difference is maintained throughout the full day remains unknown. We compared 12-h blood glucose profiles from 10 healthy males native residents at HA (3250 m) and 8 male residents at SL. Glucose profile at HA was lower throughout the glucose monitoring than that at SL (mean profile: 50.6 +/- 3.7 and 73.4 +/- 4.0 mg/dL, respectively; p < 0.001). Basal and postprandial insulin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
31
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 16 publications
8
31
0
4
Order By: Relevance
“…The enhanced effect of high altitude on not only blood pressure 22) but CAVI 5,23) in Mongolia has been reported. The lowered effect of high altitude on plasma glucose has also been reported 24) , and in fact our studied Mongolian DM patients had lower glucose levels. From the biological viewpoint in association with altitude, an increase in oxidative stress (via reactive oxygen metabolism) in Mongolian people compared with Japanese people 25,26) has been reported, and this may cause differences in atherosclerotic parameters 27) .…”
Section: Discussionsupporting
confidence: 83%
“…The enhanced effect of high altitude on not only blood pressure 22) but CAVI 5,23) in Mongolia has been reported. The lowered effect of high altitude on plasma glucose has also been reported 24) , and in fact our studied Mongolian DM patients had lower glucose levels. From the biological viewpoint in association with altitude, an increase in oxidative stress (via reactive oxygen metabolism) in Mongolian people compared with Japanese people 25,26) has been reported, and this may cause differences in atherosclerotic parameters 27) .…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, this finding corroborates the association Brought to you by | Penn State -The Pennsylvania State University Authenticated Download Date | 5/25/15 8:05 PM observed in sea-level populations [33,34]. This finding is interesting because life at high altitude is associated with an increase in insulin sensitivity [35], and for such reason the rates of type 2 diabetes mellitus are lower in the highlands [24]. Our results suggest that increased levels of γGT may modify this protection in subjects at high altitude and so increase their risk of glucose intolerance and/or type 2 diabetes mellitus.…”
Section: Characteristicssupporting
confidence: 87%
“…Srivastava et al (1974) found the lower FPG levels in 6 high altitude natives. Similarly, Castillo et al (2007) found that 10 high altitude natives had a lower blood glucose profile than sea level residents throughout 12 hours of continuous monitoring. In contrast, Sawhney et al (1991) found no difference between the fasting glucose concentrations in 15 high altitude natives compared to the values of sojourners at sea level.…”
Section: Discussionmentioning
confidence: 91%